2013
DOI: 10.5455/jva.20130219032609
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cage Floor Type on Behavior and Performance of Growing Rabbits

Abstract: Twenty four New-Zealand White rabbits of both genders (12 males and 12 females), 4 weeks old, with nearly equal body weight at the beginning of the experiment, were randomly allotted to three groups of 8 rabbit each (4 males and 4 females). Three groups were established according to the cage floor type. The first group was raised on wire mesh cage floor throughout the experiment. The second group was raised on plastic hollow mat and the third was on rubber hollow mat. Rabbits were weighed at the beginning of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
2
3
0
1
Order By: Relevance
“…Circling and biting are usually considered stereotypical behaviors of captive rabbits ( Trocino et al , 2019 ; Seidel, Beaton & Teague, 1979 ), and the decreased circling and biting behaviors among the EE-cohort rabbits may suggest that the EE re-directed the rabbits’ attention. These findings support those of previous studies, which showed that EE reduced abnormal behavior in growing rabbits ( Mohammed & Nasr, 2017 ; Abdelfattah et al, 2013 ). We believe this is because EE relieved boredom and satisfied ethological needs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Circling and biting are usually considered stereotypical behaviors of captive rabbits ( Trocino et al , 2019 ; Seidel, Beaton & Teague, 1979 ), and the decreased circling and biting behaviors among the EE-cohort rabbits may suggest that the EE re-directed the rabbits’ attention. These findings support those of previous studies, which showed that EE reduced abnormal behavior in growing rabbits ( Mohammed & Nasr, 2017 ; Abdelfattah et al, 2013 ). We believe this is because EE relieved boredom and satisfied ethological needs.…”
Section: Discussionsupporting
confidence: 93%
“…Direct focal observations of rabbits in their home cages were conducted to record different behaviors for 15 consecutive days throughout the experimental period ( Abdelfattah et al, 2013 ). After the preliminary experiment, the behavioral observations began on the 16th day of the experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The display of investigatory and locomotory behaviors was the greatest during the first and the last hour of the light and dark periods, respectively, a finding that is in accordance with Abdelfattah et al [29] who have shown that weaned rabbits move and explore more early in the morning compared to the other periods of the day. The ancestor of the domesticated rabbit, the European wild rabbit, is mainly active during the dusk, night and dawn, because as a prey-animal its chances to escape from predators are higher during these time periods of the day [30].…”
Section: Behavioral Recordings Of Offspring In Their Cagessupporting
confidence: 87%
“…Only the wooden floor and layer of straw resulted in a lower daily gain. Also, Abdelfattah et al [10] did not find differences in growing performance and behavior between rabbits kept on wire mesh, plastic slatted floor (1.5 cm slot width), and slatted floor from rubber (1.5 cm slot width). Lang [11] and Wagner et al [12] had already demonstrated that a plastic grid with a slot width of 13 mm and a slat width of 5 mm (perforation rate of approx.…”
Section: Introductionmentioning
confidence: 99%